COVID-19 Vaccination in Developing Nations: Challenges and Opportunities for Innovation - Abu Baker Sheikh; Suman Pal; Nismat Javed; Rahul Shekhar (MDPI AG, 2021)
Vaccines offer a hope toward ending the global pandemic caused by SARS-CoV2. Mass vaccination of the global population offers hope to curb the spread. Developing nations, however, face monumental challenges in procurement, allocation, distribution and uptake of vaccines. Inequities in vaccine supply are already evident with resource-rich nations having secured a large chunk of the available vaccine doses for 2021. Once supplies are made available, vaccines will have to be distributed and administered to entire populations-with considerations for individual risk level, remote geography, cultural and socio-economic factors. This would require logistical and trained personnel support that can be hard to come by for resource-poor nations. Several vaccines also require ultra-cold temperatures for storage and transport and therefore the need for specialized equipment and reliable power supply which may also not be readily available. Lastly, attention will need to be paid to ensuring adequate uptake of vaccines since vaccine hesitancy has already been reported for COVID vaccines. However, existing strengths of local and regional communities can be leveraged to provide innovative solutions and mitigate some of the challenges. Regional and international cooperation can also play a big role in ensuring equity in vaccine access and vaccination.